2021
DOI: 10.1021/acs.nanolett.1c01592
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration Behavior of Cu Nanowires under Carbon Dioxide Environment: An In Situ/Operando Study

Abstract: Copper (Cu) is a catalyst broadly used in industry for hydrogenation of carbon dioxide, which has broad implications for environmental sustainability. An accurate understanding of the degeneration behavior of Cu catalysts under operando conditions is critical for uncovering the failure mechanism of catalysts and designing novel ones with optimized performance. Despite the widespread use of these materials, their failure mechanisms are not well understood because conventional characterization techniques lack th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…In another in situ/operando S/TEM study of Cu nanowires (NWs) under CO 2 atmosphere, a degeneration behavior of Cu NWs is revealed by tracking the failure process of the catalysts under CO 2 atmosphere. [ 184 ] These studies highlight the fact that in‐situ TEM techniques have found applications in determining the structural changes of catalysts under CO 2 reduction conditions.…”
Section: Heterogeneous Catalysts Under Gaseous Reactant Reaction Cond...mentioning
confidence: 99%
“…In another in situ/operando S/TEM study of Cu nanowires (NWs) under CO 2 atmosphere, a degeneration behavior of Cu NWs is revealed by tracking the failure process of the catalysts under CO 2 atmosphere. [ 184 ] These studies highlight the fact that in‐situ TEM techniques have found applications in determining the structural changes of catalysts under CO 2 reduction conditions.…”
Section: Heterogeneous Catalysts Under Gaseous Reactant Reaction Cond...mentioning
confidence: 99%
“…One of the ideal strategies is to introduce a second metal into Pd catalysts to form bimetallic Pd-based alloy catalysts. Numerous experiments verified that bimetallic Pd-based alloy catalysts exhibit a synergistic effect that can dramatically improve the H 2 -sensing properties of bare Pd catalysts. However, SMO-based gas sensors are always operated at high temperatures of up to hundreds of degrees Celsius in air, which causes Pd-based catalyst deactivation or deterioration. To reveal the deactivation mechanism, the morphological/structural evolution of bimetallic catalysts under the operating conditions of H 2 sensors must be characterized in situ . However, carrying out in situ characterization of bimetallic catalysts with conventional analysis methods such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD) is still challenging. …”
mentioning
confidence: 99%
“…For example, the combination of gas supply and high temperature heating capability allows for growth of nanomaterials in micron-sized reactors inside the TEM, 1 inducing preferential oxidation in alloys, 2,3 and examining structural robustness and stability of catalyst materials under various corrosive environments. 4,5 Additionally, the electrochemical signal can be also monitored during reactions introduced by external gaseous species, providing the possibility to characterize structure−functional relationships for catalysis, metal-air battery, and gas sensor development based on a similar environmental system. 6 Introducing the gas or vapor phase sample into the specimen chamber is usually achieved by either creating a pressure gradient using a differential pumping system (environmental (S)TEM; E (S)TEM) 7,8 or encapsulation using electrontransparent membranes such as silicon nitride or graphene (environmental cell (S)TEM; E-cell (S)TEM) 9,10 (Table 1).…”
mentioning
confidence: 99%
“…Thanks to the implementation of a localized sealed reaction environment, in situ gas electron microscopy has gradually become an essential technique for visualizing nanoscopic reactions in real time (and often in real-space). For example, the combination of gas supply and high temperature heating capability allows for growth of nanomaterials in micron-sized reactors inside the TEM, inducing preferential oxidation in alloys, , and examining structural robustness and stability of catalyst materials under various corrosive environments. , Additionally, the electrochemical signal can be also monitored during reactions introduced by external gaseous species, providing the possibility to characterize structure–functional relationships for catalysis, metal-air battery, and gas sensor development based on a similar environmental system …”
mentioning
confidence: 99%